The preparation of physical education students for health education lessons – theory and reality - Klimas, Nela; Laudańska-Krzemińska, Ida (Quality in Sport, 2015)
The aim of the study was to confront the requirements of the new core curriculum, changing the status of school-based health education and linking it strongly with physical education (PE), with the actual preparation of students to conduct health education lessons. The survey was conducted in the academic year 2014/2015 at the Eugeniusz Piasecki University of Physical Education in Poznan, among 51 physical education master’s students. The diagnostic survey method based on the authorial and anonymous questionnaire was used. According to the study results one of the most challenging tasks of future PE teacher are those connected with psychosocial health and developing life skills among children and youth.